The utilization of comics in the teaching of the human rights concept - TUNCEL, GÜL (ELSEVIER SCIENCE BV, 2010)
The comics catch attention of the children with the humorous side. On the other hand, according to the learning theories, creative activities make the learning more effective. Again, the creation requires one's making synthesis. The creativity in learning depends on working with various instruments and thinking according to the problem solving methods. That is why, it is useful to benefit from comics to make it gained especially the abstract concepts as human rights concept in Social Studies lesson. In this context, the problem of the research is to determine the effect of the comics in teaching the human rights concept. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Social studies teaching; comics; human rights